Transformasi Limbah Menjadi Hijau: Revitalisasi Taman Desa Sukaresmi Melalui Pengelolaan Limbah - Titin Sunaryati; Ira Restu Kurnia; Bramianto Setiawan; Dina Cameliya; Erlinawati Erlinawati; Santi Sri Lestari; Rizqi Romadon (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Desa Sukaresmi, located in the Cikarang Selatan sub-district of Bekasi Regency, West Java, has experienced rapid population growth in tandem with industrial development in its vicinity Although this increase has brought positive economic impacts, environmental issues, particularly waste management, pose significant challenges The lack of innovation in managing organic and non-organic waste has led to environmental pollution and the loss of green spaces The Real Work Lecture Program (KKN) in Desa Sukaresmi proposes a solution by transforming waste into green elements through the revitalization of the village park Organic waste will be processed into compost to enrich the soil, while non-organic waste will be recycled into park decorations. This program aims to enhance collective awareness among residents about the importance of waste management and environmental preservation, making Desa Sukaresmi a pioneer in sustainable waste management practices that can be emulated by other villages The method used in this service is direct observation in Desa Sukaresmi The results obtained from this service include the revitalization of a beautiful village park in front of the Desa Sukaresmi office, with a satisfaction rating of 90% from the community of Desa Sukaresmi.